2020
DOI: 10.1016/j.iotech.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-reactive B cells and antibody responses after allogeneic haematopoietic cell transplantation

Abstract: For many high-risk haematologic malignancies, such as acute myeloid leukaemia, the success of therapy relies mainly on invoking a curative antitumour immune response. This can be achieved by inducing a graft-versus-leukaemia response following allogeneic haematopoietic cell transplantation. While the contribution of T cells and natural killer cells to graft-versus-leukaemia responses is established, the contribution of B cells and antibodies is relatively unexplored. This article reviews what is known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…We also found that B-cell reconstitution was associated with lower risk of relapse. This may be explained by the involvement of B cells in graft-versusleukemia effect and antitumor immunity after allo-HSCT [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that B-cell reconstitution was associated with lower risk of relapse. This may be explained by the involvement of B cells in graft-versusleukemia effect and antitumor immunity after allo-HSCT [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…This may have relevance beyond solid organ transplantation, most immediately in mixed chimeric states that typically develop following after reduced intensity conditioning and hematopoietic stem cell transplantation for hematological malignancies. The co-existence of donor and recipient lymphocyte fractions may promote spontaneous humoral immunity; indeed, isolated reports describe the generation of anti-tumor antibodies associated with hematopoietic mixed chimerism (8).…”
Section: What Is the Clinical Relevance Of Inverted Direct Allorecogn...mentioning
confidence: 99%
“…It is thought that the GVL effect is mediated predominantly by T cells but can also be mediated by natural killer (NK) cells and B cells, and cytokines produced by these cells. 2,7,8 The pathogenesis of GVHD is also mediated predominantly by T cells. As such, one therapeutic strategy for GVHD prevention is the use of post-transplant cyclophosphamide (PTCy), a cytotoxic compound often administered at 50 mg kg À1 on days 3 and 4 post-donor HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…The GVL effect was first observed over 60 years ago, 6 yet despite years of preclinical and clinical studies, the precise mechanism required to achieve GVL immunity without promoting GVHD has not been uncovered. It is thought that the GVL effect is mediated predominantly by T cells but can also be mediated by natural killer (NK) cells and B cells, and cytokines produced by these cells 2,7,8 . The pathogenesis of GVHD is also mediated predominantly by T cells.…”
Section: Introductionmentioning
confidence: 99%